Niche breadth and species richness: Correlation strength, scale and mechanisms. Issue 1 (17th September 2019) - Granot, Itai; Belmaker, Jonathan
Abstract: Aim: It is often assumed that species in richer sites are more specialized, but empirical studies show conflicting results. In the present study, we quantify the correlation between community‐level niche breadth and richness. We contrast three mechanisms for gradients in niche breadth: climate, community assembly and nested interactions. First, the climatic stability within the tropics enables species to specialize, resulting in high richness. Under this scenario, we predict stronger richness–niche breadth correlations over larger latitudinal extents and when using environmental niche breadth measures (e.g., habitat). Second, in species‐rich areas, biotic interactions drive species to specialize. This may yield richness–niche breadth correlations regardless of the latitudinal extent and the type of niche breadth measure examined, whether environmental or functional (e.g., diet). Third, increased richness intensifies interactions between extreme specialists and generalists. Here, we predict stronger richness–niche breadth correlations when using functional niche breadth measures. Location: Global. Time period: 1973–2018. Major taxa studied: Many taxa. Methods: We conducted a meta‐analysis, with the effect size estimated as the correlation between richness and community‐averaged niche breadth extracted from each study. We also examined how these correlations depend on the niche breadth measure used (environmental or functional), scale (grain and latitudinal extent), ecosystem and taxa. Results: We found a strong negative correlation between richness and niche breadth, and overall, a non‐significant correlation between latitude and niche breadth. The richness–niche breadth correlation was independent of the niche breadth measure used (environmental or functional). Scale, ecosystem and taxa had little effect on the strength of the correlation. Main conclusions: We confirm that species in richer sites, but not necessarily in the tropics, are more specialized. This finding is not dependent on scale or on the type of niche breadth measure used. These results suggest that high richness drives community‐level specialization, and thus community assembly is likely to be the major driver of niche breadth rather than climatic gradients shaping both niche breadth and richness.